2002
DOI: 10.1086/339251
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Gene for Peripheral Arterial Occlusive Disease to Chromosome 1p31

Abstract: Peripheral arterial occlusive disease (PAOD) results from atherosclerosis of large and medium peripheral arteries, as well as the aorta, and has many risk factors, including smoking, diabetes, hypertension, and hyperlipidemia. PAOD often coexists with coronary artery disease and cerebrovascular disease. Cross-matching a population-based list of Icelandic patients with PAOD who had undergone angiography and/or revascularization procedures with a genealogy database of the entire Icelandic nation defined 116 exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 15 publications
1
37
0
4
Order By: Relevance
“…Putting aside theoretical arguments, the suitability of the Icelandic population for genemapping studies is now perhaps best judged by results; see, for example, Stefánsson et al (2003), Hicks et al (2002), Grétarsdóttir et al (2002) and Gudmundsson et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Putting aside theoretical arguments, the suitability of the Icelandic population for genemapping studies is now perhaps best judged by results; see, for example, Stefánsson et al (2003), Hicks et al (2002), Grétarsdóttir et al (2002) and Gudmundsson et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…The control group for the SNP association study was population-based and comprised of 624 unrelated males and females 20-90 years of age whose medical history was unknown. The stroke and PAOD cohorts used in this study have previously been described [32][33][34] . For the stroke linkage analysis, we used genotypes from 342 males with ischemic stroke or TIA that were linked to at least one other male within and including six meioses in 164 families.…”
Section: Study Populationmentioning
confidence: 99%
“…We are aware of only 1 study, a familybased linkage study that identified a genetic locus conferring susceptibility to PAD. 31 Gudmundsson et al 31 identified a locus mapping to human chromosome 1p31 termed PAOD1. One of the strengths of this study is that it took an unbiased approach, starting with the PAD phenotype, to identify novel genetic risk factors rather than starting with a potentially biased list of candidate genes.…”
Section: Days Post Surgerymentioning
confidence: 99%